Biện pháp phát triển đội ngũ tổ trưởng chuyên môn ở các trường mầm non công lập: Nghiên cứu tại thành phố Nha Trang, tỉnh Khánh Hòa - Nguyễn Sỹ Thư; Nguyễn, Thị Mai Linh (Tạp chí Giáo dục, 2025)
Professional groups in preschools serve as fundamental units directly responsible for the implementation and management of specialized activities, playing a crucial role in the overall educational outcomes of the school. At the helm of each professional group is the head of the group, who holds a significant role and is often seen as the extended arm of the principal, managing professional tasks on behalf of the principal within the school’s specialized department. The group leader is accountable to the principal for the quality of education provided by the group. This study proposes six measures to develop the team of professional group leaders in public preschools in Nha Trang City, Khanh Hoa Province. Implementing these measures systematically, comprehensively, and flexibly, according to the conditions of each school, will create positive changes in the management and development of professional group leaders in public preschools in Nha Trang. This, in turn, will meet the requirements for fundamental and comprehensive reforms in education during the current period.